The young mathematician's guide : being a plain and easy introduction to the mathematicks. In five parts. Viz. I. Arithmetick, Vulgar and Decimal, with all the useful Rules ; And a General Method of Extracting the Roots of all Single Powers. II. Algebra, or Arithmetick in Species ; wherein the Method of Raising and Resolving Equations is rendered Easy ; and illustrated with Variety of Examples, and Numerical Questions. Also the whole Business of Interest and Annuities, &c. performed by the Pen. III. The Elements of Geometry, contracted, and Analytically demonstrated ; with a new and easy Method of finding the Circle's Periphery and Area to any assigned Exactness, by one Equation only: Also a new way of making Sines and Tangents. IV. Conick Sections, wherein the chief Properties, &c. of the Ellipsis, Parabola, and Hyperbola, are clearly demonstrated. V. The Arithmetick of Infinites explained, and rendered Easy ; with it's Application to superficial and solid Geometry. With an appendix of practical gauging / by John Ward. - Ward, John, active 1698-1709. (Tufts University. Tisch Library., 2015)
The tenth edition, carefully corrected / to which is added, a supplement, containing the history of logarithms and an index to the whole Work.; 1 online resource ([8], 480, [8] pages) : illustrations.; Pages 433-480 contain 'An appendix of practical gauging' and the supplement.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: English Short Title Catalog, T132404